Peroxidase-like activity of citrate-functionalized magnetite nanoparticles augmented its antibacterial potency - Haitham Al-Madhagi; Abd Alraouf Tarabishi; Fatima Al-Zahra Hamsho; Zaher Tahan; Lama Alchab; Wassim Abdelwahed (Results in Chemistry)
The classic utilization of nanomaterials has now transformed to serve enzyme-like activities (nanozymes) that found different applications, particularly as antibacterial agents. Here, we report the synthesis of citrate-functionalized iron oxide nanoparticles (IOMNPs) and the subsequent utilization of its peroxidase-like activity as antibacterial agent. The nanoparticles were prepared using coprecipitation method and characterized using UV–visible spectrophotometry, Fourier-transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), zeta potential, magnetism and atomic force microscopy (AFM). The catalytic activity was assessed by its ability to oxidize pyrogallol. Finally, this nanozyme properties were harnessed for potential antibacterial potency. Gram-positive bacterium Staphylococcus aureus, and Gram-negative bacterium, Escherichia coli, using the Kirby-Bauer disk diffusion method. DLS analysis demonstrated a diameter of 93 nm of the synthesized nanoparticles and the structure revealed by AFM proved the nanooval appearance. The prepared nanozymes exhibited a zeta potential of −27.8 mV, strong magnetic behavior, and prominent peroxidase-like activity. Their testing as antibacterial agents showed enhanced efficacy when hydrogen peroxide was introduced at a volumetric ratio of 25 µL:75 µL against both strains. In conclusion, citrate-decorated IOMNPs deserves further examination on antibiotic resistant strains and subsequent in vivo models as a novel antibacterial agent.